How to Say Ã¢â¬ÅThanksÃ¢â¬Â in English - Fachrurrazy Fachrurrazy (TEFLIN, 2004)
Thanks is a very common expression in English. However, many English learners do not often use it. Very often, English teachers only teach their students how to pronounce the expression with some samples of situation. They do not explain why and when the native speakers of English say thanks . This article presents the usage and use of the expression, which is much related to the English culture. The discussion includes implications to TEFL.